STATUS PRAWNY FUNDUSZY CELOWYCH - Kucia-Guściora, Beata (Wydział Prawa i Administracji UAM, 2004)
Earmarked funds are mentioned in the Polish Public Finances Act as one of the five organisational legal forms of budget management. This article deals with their legal status. Establishing the legal status of earmarked funds requires a comparative analysis based on administrative and tax law. As an introduction the author discussed the notion of a fund both in colloquial and legal language. Next she analysed the dogmatic and legal definition of this notion on the basis of regulations in force and the doctrine of financial law, pointing to inaccuracies in legal regulations. As a result there are considerable interpretative difficulties e.g. in establishing a catalogue of earmarked funds. From the financial and legal point of view it was necessary to consider the legal nature c f revenue and expenditure and the nature of financial plan of earmarked funds. The relation between plans of earmarked funds and budgetary acts and resolutions was also emphasised. The issues of the legal from of earmarked funds and the nature of property administered by the funds required a civil legal analysis. The analysis of administrative legal status of earmarked funds is based on the organisational and territorial structures of particular funds, the nature and competence of fund agencies. It seems that the essence of funds was not taken into consideration properly in the Polish tax law. Earmarked funds functioning on the basis of regulations in the Public Finances Act enjoy exemption from tax. Still, the way the issue is settled is debatable. Legal forms on which earmarked funds are based are non-uniform and casuistic. For that reason establishing a catalogue of universal legal properties of earmarked funds is problematic.
THE LEGAL STATUS OF EARMARKED FUNDS